KAJIAN PENDAPATAN DAN KONTRIBUSI USAHATANI KELAPA (Cocos Nucifera) TERHADAP PENDAPATAN KELUARGA PETANI DI KABUPATEN TANJUNG JABUNG BARAT, PROVINSI JAMBI - Nida Kemala (Universitas Batanghari Jambi, 2015)
The objective of this research is to determine the income contribution of coconut farming on total farmer income at Tanjung Jabung Barat District, Jambi Province. Survey method was used that completed by descriptif analization. It took 15% sample so there are 73 samples (481 populations) that taken by combaining stratified random sampling and two stage random sampling. The result of this research showed that the total fixed cost was Rp.4.888/month while the total variable cost was . So that the total production cost was Rp. 551.796/month. Meanwhile the average revenue of coconut farming was Rp. 2.463.388/month, so that the average income received from coconut farming was Rp. 1.911.592/month. .the income outside of coconut farming was Rp. 4.546.575/month. Accordingly the last information showed that income contribution of coconut farming on the total farmer income was 42%.Key word : Coconut farming, contribution, income.